Efficacy of GC-376 against SARS-CoV-2 virus infection in the K18 hACE2 transgenic mouse model - C. Joaquín Cáceres (Nature Portfolio, 2021)
Abstract The COVID-19 pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is the defining global health emergency of this century. GC-376 is a Mpro inhibitor with antiviral activity against SARS-CoV-2 in vitro. Using the K18-hACE2 mouse model, the in vivo antiviral efficacy of GC-376 against SARS-CoV-2 was evaluated. GC-376 treatment was not toxic in K18-hACE2 mice. Overall outcome of clinical symptoms and survival upon SARS-CoV-2 challenge were not improved in mice treated with GC-376 compared to controls. The treatment with GC-376 slightly improved survival from 0 to 20% in mice challenged with a high virus dose at 105 TCID50/mouse. Most notably, GC-376 treatment led to milder tissue lesions, reduced viral loads, fewer presence of viral antigen, and reduced inflammation in comparison to vehicle-treated controls in mice challenged with a low virus dose at 103 TCID50/mouse. This was particularly the case in the brain where a 5-log reduction in viral titers was observed in GC-376 treated mice compared to vehicle controls. This study supports the notion that GC-376 represents a promising lead candidate for further development to treat SARS-CoV-2 infection and that the K18-hACE2 mouse model is suitable to study antiviral therapies against SARS-CoV-2.